Effect of different amounts of Pt on Fe3O4−TiO2 for photocatalytic H2 production under solar light - KERKEZ KUYUMCU, ÖZGE (My University, 2023)
In this study, Pt doped Fe3O4−TiO2 photocatalysts were synthesized in two steps; (i) Fe3O4−TiO2 (FT) was prepared by the complex-assisted vapor thermal (VT) method, (ii) Pt was doped to Fe3O4−TiO2 (FT−Pt) by the polyol method. The effect of different amounts of Pt was investigated for photocatalytic hydrogen production. The absorption spectrum of FT with 5.0 % Pt exhibits a surface plasmon resonance (SPR) peak of ∼420 nm which corresponds to the band gap of 2.95 eV. The FT and Pt doped FT samples showed a less intense photoluminescence (PL) band than TiO2 (T) due to the lower e−/h+ recombination rate. By increasing % wt. Pt in the FT samples, PL intensity was decreased. Thus, Pt plays an essential role to hinder the recombination of e−/h+ pairs. Consequently, FT-5.0 % Pt showed 144 μmol/g-cat H2 production rate, just about 3.3 times higher than that of FT photocatalyst; due to the suitable band gap energy and the retarded e−/h+ recombination. Therefore, the synergistic effect of Pt and Fe3O4 is found to be beneficial to decrease the e−/h+ recombination rate thus the photocatalytic activity enhancement was achieved.
Keywords: Kimya; Temel Bilimler; Chemistry; Natural Sciences; Temel Bilimler (SCI); Natural Sciences (SCI); CHEMISTRY; Genel Kimya; Fizik Bilimleri; General Chemistry; Physical Sciences; Fe3O4−TiO2; Hydrogen (H2) production; Photocatalysis